Ergonomic risk assessment of musculoskeletal disorders during chest compression at kneeling, standing and step-on-stool position in rescuer performing cardiopulmonary resuscitation - Ghani, Nurul Husna Abd. (2020)
Introduction: Countless research has been carried out to improve the quality of cardiopulmonary resuscitation (CPR) delivered to the patient but there is scarce data concerning health impact of CPR upon person performing it. Objectives: The aim of this study was to determine the ergonomic risk of musculoskeletal disorders (MSD) in rescuer performing CPR at 3 different positions: kneeling, standing, standing on step-stool, quality of CPR performed at each position and their correlations. Methods: A cross-sectional simulated-manikin study of in-hospital cardiac arrest was conducted among medical personnel of emergency department of university hospital located in Kelantan, Malaysia. Rapid Entire Body Assessment (REBA) score as a universal tool for ergonomic assessment was used in this study. Results: In total, 67 participants took part in this study. Kneeling showed the worst mean REBA score of 9.00 (1.00) with high risk of developing MSD, followed by step-on-stool 7.63 (1.54) and standing position 7.00 (1.00) which account for moderate risk. Significant difference were observed in compression depth between kneeling and standing position (p<0.001, mean difference (95% CI) = 6.27 (3.26, 9.28)), and between kneeling and step-onstool (p<0.001, mean difference (95% CI) = 4.35 (2.21, 6.49)). There is no evidence of significant correlation between REBA risk group and CPR quality at standing position and kneeling position, although at step-on-stool position significant correlation noted between REBA risk group and complete recoil. Conclusion: There is notable risk of developing MSD in person performing CPR at 3 different positions although no remarkable correlation between the risk and quality of CPR performed.